Effects of Dietary Rutin Supplementation on the Intestinal Morphology, Antioxidant Capacity, Immunity, and Microbiota of Aged Laying Hens - Hengzhi Li; Yunfeng Gu; Rui Jin; Qingfen He; Yanmin Zhou (MDPI AG, 2022)
This research investigated the effects of dietary rutin supplementation on the intestinal morphology, antioxidant capacity, immunity, and microbiota of aged laying hens. The results showed that 500 mg/kg rutin supplementation increased the villus height of jejunum (P < 0.05). Rutin affected the immune system of the ileum and the jejunum. In the jejunum, a diet with 500 mg/kg rutin supplementation enhanced secretory immunoglobulin A (sIgA) and reduced tumor necrosis factor-<semantics>α</semantics> (TNF-<semantics>α</semantics>) levels (P < 0.05). A diet with 1000 mg/kg rutin supplementation increased jejunal sIgA, immunologlobulin M (IgM), and interleukin-4 (IL-4) levels while decreasing interleukin-1<semantics>β</semantics> (IL-1<semantics>β</semantics>), TNF-<semantics>α</semantics>, and interferon-<semantics>γ</semantics> (IFN-<semantics>γ</semantics>) levels (P < 0.05). Meanwhile, a diet with 500 mg/kg rutin increased sIgA, immunologlobulin G (IgG), IgM, and interleukin-10 (IL-10) levels and reduced TNF-<semantics>α</semantics> and IFN-<semantics>γ</semantics> levels in the ileum (P < 0.05). In the ileum, a diet with 1000 mg/kg rutin supplementation raised sIgA, IgG, IgM, IL-4, and IL-10 levels while decreasing IL-1<semantics>β</semantics>, TNF-<semantics>α</semantics>, and IFN-<semantics>γ</semantics> levels (P < 0.05). At the family level, a diet with 500 mg/kg rutin supplementation raised the relative abundance of Monoglobaceae and decreased the relative abundance of Eubacteriaceae (P < 0.05) compared to the control group. In the 1000 mg/kg rutin group, the relative abundance of Lactobacillaceae and Unclassified Coriobacteriale was considerably lower and the relative abundance of Monoglobaceae was higher than the control group (P < 0.05). This study showed that a diet with rutin supplementation can improve the intestinal health of aged laying hens, and the mechanism is related to improving the intestinal morphology and intestinal immune status, and regulating the intestinal microbes.